Interferensi Bahasa Jawa dalam Bahasa Arab: Kasus pada Jamaah Yasin dan Tahlil Desa Crabak - Anggian, Lutvi Ali Sahana; Nurcahyaningtias, Novia Dwi (Proceedings of Annual Conference for Muslim Scholars, 2024)
The interference of Javanese in Arabic in the yasin and tahlil congregation can be heard clearly in the pronunciation. Many members of the congregation adopted Arabic vocabulary, changing pronunciation and sentence structure to suit Javanese customs. For example, in prayer or dhikr, the pronunciation can sound more "Javanese," potentially affecting understanding of the original meaning. Apart from that, the mixture of Javanese terms in Arabic expressions also creates local nuances that enrich religious practices. This phenomenon shows dynamic cultural interactions in a spiritual context. The aims of this research are: 1) forms and types of Javanese language interference in Arabic: the case of the Yasin and tahlil congregation in Crabak Village, 2) factors causing language interference, 3) efforts to minimize it. This research uses descriptive qualitative. The method used is the listening and note-taking method to collect data and the comparison technique to analyze the data. The results of this research: 1) there were several cases of language errors consisting of phonological interference, 2) the factors causing the interference were the bilingualism of the Yasin and Tahlil congregation mothers, differences in the B1 and B2 systems, carrying over B1 habits when producing B2, 3) with correct imitation of Arabic phonemes.